Asymptomatic Malaria Infection Is Maintained by a Balanced Pro- and Anti-inflammatory Response - Frimpong, Augustina; Amponsah, Jones; Adjokatseh, Abigail Sena; Agyemang, Dorothy; Bentum-Ennin, Lutterodt; Ofori, Ebenezer Addo; Kyei-Baafour, Eric; Akyea-Mensah, Kwadwo; Adu, Bright; Mensah, Gloria Ivy; Amoah, Linda Eva; Kusi, Kwadwo Asamoah (Frontiers in Microbiology, 2020)
Background: Pro- and anti-inflammatory cytokines are important mediators of immunity and are associated with malaria disease outcomes. However, their role in the establishment of asymptomatic infections, which may precede the development of clinical symptoms, is not as well understood. Methods: We determined the association of pro and anti-inflammatory cytokines and other immune effector molecules with the development of asymptomatic malaria. We measured and compared the plasma levels of proinflammatory mediators including tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ), interleukin (IL)-6, IL-12p70, IL-17A and granzyme B, the anti-inflammatory cytokine IL-4 and the regulatory cytokine IL-10 from children with asymptomatic malaria infections (either microscopic or submicroscopic) and uninfected controls using Luminex. Results: We show that individuals with microscopic asymptomatic malaria had significantly increased levels of TNF-α and IL-6 compared to uninfected controls. Children with either microscopic or submicroscopic asymptomatic malaria exhibited higher levels of IFN-γ, IL-17A and IL-4 compared to uninfected controls. The levels of most of the pro and anti-inflammatory cytokines were comparable between children with microscopic and submicroscopic infections. The ratio of IFN-γ/IL-10, TNF-α/IL-10, IL-6/IL-10 as well as IFN-γ/IL-4 and IL-6/IL-4 did not differ significantly between the groups. Additionally, using a principal component analysis, the cytokines measured could not distinguish amongst the three study populations. This may imply that neither microscopic nor submicroscopic asymptomatic infections were polarized towards a pro-inflammatory or anti-inflammatory response. Conclusion: The data show that asymptomatic malaria infections result in increased plasma levels of both pro and anti-inflammatory cytokines relative to uninfected persons. The balance between pro- and anti-inflammatory cytokines are however largely maintained and this may in part, explain the lack of clinical symptoms. This is consistent with the generally accepted observation that clinical symptoms develop as a result of immunopathology involving dysregulation of inflammatory mediator balance in favour of pro-inflammatory mediators.